An evaluation of the effectiveness of an inflation targeting strategy in Turkey - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
In this research, the performance of inflation targeting strategy was analysed using the least square method (LSM) with the regression model for economic circumstances in Turkey. The results of this research can be summarised as follows: (1) Inflation targeting regime has a weak positive effect on inflation rate performance; (2) There is no significant relationship between inflation targeting regime and growth rate; (3) There is a positive but a weak relationship between inflation targeting regime and exchange rate performance; and (4) Inflation targeting regime has a strong positive effect on nominal interest rate performance. Thus, these results support the argument in the literature that inflation targeting affects macroeconomic performance positively except for growth rate'. Thus, the post-2002 inflation-targeting regime, whether rule-based or occasional, has led to some improvements in other macroeconomic indicators, even though the primary aim of monetary policy instruments is to bring down the rate of inflation. Such stability-assuring policies enable investors to invest in a more trustable environment.
Keywords: Inflation; inflation targeting; price stability; performance analysis; AUTOREGRESSIVE TIME-SERIES; UNIT-ROOT